C1q/TNF-related protein 1 prevents neointimal formation after arterial injury. (February 2017) - Kanemura, Noriyoshi; Shibata, Rei; Ohashi, Koji; Ogawa, Hayato; Hiramatsu-Ito, Mizuho; Enomoto, Takashi; Yuasa, Daisuke; Ito, Masanori; Hayakawa, Satoko; Otaka, Naoya; Murohara, Toyoaki; Ouchi, Noriyuki
Abstract: Background and aims: Obesity contributes to the progression of vascular disorders. C1q/TNF-related protein (CTRP) 1 is a circulating adipokine, which is upregulated in obese complications including coronary artery disease. Here, we investigated the role of CTRP1 in regulation of vascular remodeling after mechanical injury and evaluated its potential mechanism. Methods: Mice were subjected to wire-induced injury of left femoral arteries. An adenoviral vector encoding CTRP1 (Ad-CTRP1) or β-galactosidase as a control was injected into the jugular vein of mice 3 days prior to surgery. Results: Systemic administration of Ad-CTRP1 to wild-type mice led to reduction of the neointimal thickening after wire-induced arterial injury and the number of bromodeoxyuridine-positive cells in injured vessels as compared with treatment with control vectors. Treatment of vascular smooth muscle cells (VSMCs) with CTRP1 protein attenuated proliferative activity and ERK phosphorylation in response to PDGF-BB. CTRP1 treatment increased cyclic AMP (cAMP) levels in VSMCs, and inhibition of adenylyl cyclase reversed the inhibitory effect of CTRP1 on VSMC growth and ERK phosphorylation. Antagonization of sphingosine-1-phosphaterote (S1P) receptor 2 blocked the effects of CTRP1 on cAMP production and VSMC growth. Furthermore, CTRP1-knockout mice had enhanced neointimal thickening following injury and increased numbers of proliferating cells in neointima compared to control WT mice. Conclusions: These findings indicate that CTRP1 functions to prevent the development of pathological vascular remodeling by reducing VSMC growth through the cAMP-dependent pathway. Highlights: Overexpression of CTRP1 resulted in reduced neointimal thickening after vascular injury and decreased cell proliferation in injured arteries. CTRP1 deficiency led to an increase in injury-induced neointimal hyperplasia and cell growth in injured vessels. CTRP1 suppressed growth factor-induced VSMC growth. The ability of CTRP1 to modulate vascular remodeling was likely to be mediated through its ability to stimulate the cAMP signaling pathway in VSMCs. CTRP1 acts as an adipokine that plays an important role in protecting the vasculature from damage.